Critical Review of Advanced Material for Transit-Oriented Development in a Hot-Humid Climate. Issue 1 (July 2020) - Rahmah, Nadiya; Wonorahardjo, Surjamanto
Abstract: Building material applied in a Transit-Oriented Development (TOD) area should meet high requirements such as having heavy-duty capacity, high durability, low maintenance, cost-effectiveness, and environmental-friendliness. In a tropical-rainforest or hot-humid climate, some of those requirements are intensified, especially those which are related to solar radiation and rainwater. Most existing urban development in a hot-humid climate must endure problems caused by uncontrolled stormwater and urban heat island (UHI). The idea of adopting a transit-oriented paradigm into the existing cities, convey a question whether the shift will be determining the liveability of the area; whether it could solve the existing problem or, on the contrary, generate additional problems. To overcome problems of an existing urban area and anticipate the requirements of a TOD area, the researcher progressively develops numerous materials under the term such as 'advanced material', 'green material', and 'smart material'. This review covers current trends in material research which is relevant for TOD in a hot-humid climate. The identified trends are analyzed to generate discussion in which the TOD planning in hot-humid climate should consider and anticipate the prospect of advanced material.